Perbandingan Varian Metode Multiscale Retinex untuk Peningkatan Akurasi Deteksi Wajah Adaboost HAAR-like - Laurentius Kuncoro Probo Saputra (Maranatha University Press, 2016)
Face detection is a popular research in image processing field. Face detection can be used in many application like multi-face recognition, video surveillance, human counter or monitoring. The famous face detection method is developed by Viola-Jones that is named Adaboost using HAAR-like feature. In many research about face detection using Adaboost HAAR-like, it is shown Adaboost HAAR-like face detection method have a limitation in low illumination. In this paper, we want to compare an improvement for increasing accuracy of face detection result using MSRCR and AMSR method. MSRCR and AMSR is an image enhancement method. Finally the results show that MSRCR is better than AMSR for increasing accuracy of face detection result. MSRCR can improve the accuracy until 1,43 times, but AMSR can only improve the accuracy until 1,11 times.